1987
DOI: 10.1104/pp.83.1.213
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Two CAM Species to Different Irradiances during Growth and Susceptibility to Photoinhibition by High Light

Abstract: Two CAM species, Kalanchoe daigremontiana Hamet et Perrier and Hoya carnosa (L.) R. Br., were grown under a range of five photon flux area densitites (PFD) and then characterized. Significant acclimation to shade was indicated by progressive decreases in leaf thickness, rates of respiratory 02 uptake, light compensation point, maximum rates of photosynthetic 02 evolution, nocturnal acid accumulation, and 653C values, and increases in chlorophyll concentration and absolute levels of room temperature (25°C) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
2

Year Published

1989
1989
2000
2000

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 13 publications
5
23
2
Order By: Relevance
“…In agreement with the findings of Greer et al (18), but in contrast to the reports of other workers (1,8,9,11,12), we obtained a curvilinear relationship between Fv/FM and 'A (Fig. 1C).…”
Section: Plantsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with the findings of Greer et al (18), but in contrast to the reports of other workers (1,8,9,11,12), we obtained a curvilinear relationship between Fv/FM and 'A (Fig. 1C).…”
Section: Plantsupporting
confidence: 93%
“…Models for energy distribution in the photochemical apparatus (10,19) have led to the prediction of a linear relationship between Fv/FM (near 690 nm) and bA (8). The results of several investigators have supported this prediction (1,8,9,11,12). However, in studies of Actinidia deliciosa, Greer et al (18) found that this relationship was curvilinear and concluded that Fv, which was linearly related to OA, provided a better estimate of the inhibitory effects of high PFD on PSII photochemistry.…”
mentioning
confidence: 84%
“…Perhaps the least equivocal indicator of PSII photochemical status is induction of chlorophyll fluorescence at 690 nm and 77 K. In particular, the ratio of variable to maximum fluorescence (Fv/Fm) following dark adaptation is correlated with quantum yield (~0), at least following short-term exposure of shade-grown plants to high PFD (Adams et al 1987a;Bj6rkman 1987;Bj6rkman and Demmig 1987;Demmig and Bjtrkman 1987). The ratio Fv/Fm can also be determined at room temperature using pulse-amplitude modulation techniques (Schreiber et al 1986).…”
Section: Introductionmentioning
confidence: 97%
“…occur in both shaded and exposed natural habitats (21), and some species such as Kalanchooe daigremontiana have a large acclimation potential with respect to growth PFD2 (1). In a recent study (18), a marked gradation in the degree of CAM was observed within the chlorenchyma of the amphistomatic leaves of K. daigremontiana.…”
mentioning
confidence: 99%
“…Light was provided by metal halide lamps (HRI-T 1000 W/D; Radium Elektrizitiits-Ges., Wipperfurth, F.R.G.). Infrared radiation was reduced using 3 mm thick 1 PFDs by varying the distance between lamps and plants and by insertion of brass screens to which a coating of carbon had been applied with a candle.…”
Section: Plant Materialsmentioning
confidence: 99%